A High-Precision Interpolation Method for Data Transfer in Fluid-Structure Interaction Analysis. (26th September 2022) - Li, Xuehua; Zhang, Lei; Wang, Peiyan; He, Xingsuo
Abstract : In order to improve the precision of data transfer in fluid-structure interaction (FSI) analysis, this paper puts forward an improved inverse isoparametric mapping (IIM) method, which can improve the load transfer accuracy by means of increasing the quantity of Gauss integral points. As displacement transfer happens, the method can perform the function of revising the displacement between the point to be interpolated and projection point, by which the example emulation is also carried out. Some practical solutions are presented, aiming to grapple with pertinent problems such as local interpolation burr and global interpolation distortion which are originated from oversimplified structure dynamic models and inconsistent structural deformation. The calculation results show that the improved IIM method has higher interpolation precision, which can consequently provide a valuable source of reference for FSI analysis by improving the precision of data transfer and satisfying the conservation of total force, total torque, and total virtual work in the meantime.